Determinants of supportive care experiences for women living with breast cancer in rural communities of British Columbia - D'Souza, Melba Sheila; Gidda, Ruby; Karkada, Subrahmanya N; Nairy, Ashwin (Canadian oncology nursing journal, 2025)
Enabling women with breast cancer to actively participate in their care requires a better understanding of the interplay between contextual factors and mediators. This research explored the determinants of supportive care experiences for women living with breast cancer in rural communities of British Columbia. The study used a quantitative, descriptive, cross-sectional design. A survey regarding demographic, health, decision support, and breast cancer supportive care experiences was administered to 100 participants. The combination of being less than 40 years old, having an undergraduate education, and being three to five years post-diagnosis is associated with higher (more positive) total survey scores. A linear combination of undergraduate school and health problems post-treatment showed higher medical treatment scores, with R = 23%. The findings emphasize the growing need for psychosocial and emotional supportive care for cancer survivors. The results highlight the potential benefits of informed decision-support tools to fortify supportive care, emphasizing the need to facilitate better supportive care services for women battling breast cancer. Supportive care plays a crucial role in guiding individuals' experiences with cancer through the healthcare system. Increasing supportive care centres, especially in rural areas, could improve patient-reported outcomes, and experiences, and ensure timely access to care.